Raquianestesia contínua com altas doses de anestésicos locais - Imbelloni, Luiz Eduardo (2010)
Background and objectives: Better control of the level, intensity, and duration of spinal analgesia represents the greatest advantages of continuous spinal anesthesia. With the advent of intermediate catheters (over-the-needle catheter) and its low incidence of headaches and neurological symptoms, the technique has been gaining credibility. The objective of this paper is to report the possible safety of the new catheter with a large dose of hyperbaric 0.5% bupivacaine with 1.6% glucose associated with hyperbaric 2% lidocaine with 1.6% glucose. Case Report: Male patient, 78 years old, 85 kg, 168 cm, physical status ASA III, with hypertension, coronary artery disease, and chronic renal failure. The patient was candidate for surgery for huge bilateral inguinal and umbilical hernias, being submitted to preoperative pneumoperitoneum for one week to stretch abdominal cavity. After venoclysis with an 18G catheter, he was monitored with cardioscope, non-invasive blood pressure, and pulse oximetry; he was sedated with 1 mg of midazolam and 100 µg of fentanyl intravenously, and placed in left lateral decubitus. He underwent continuous spinal anesthesia by a median puncture in L3-L4 with a set with a 27G cut-bevel needle and 22G catheter. The total dose of anesthetic used was 25 mg of 0.5% bupivacaine (hyperbaric, with 1.6% glucose), 160 mg of 2% lidocaine (hyperbaric, with 1.6% glucose), and morphine (100 µg). The patient was followed-up until the 30th postoperative day without neurological complaints. Conclusions: Recently, the poor distribution of the local anesthetic through the microcatheter was attributed as the cause of cauda equina syndrome. This case report showed that, with the administration of high doses of hyperbaric anesthetics through the new catheter, poor distribution or risk of cauda equina syndrome were not observed.